Effects of in-hospital breast feeding on brain function development in preterm infants in China: study protocol for a prospective longitudinal cohort study - Yao Zhang; Rui Yang; Hua Wang; Xinfen Xu (BMJ Open)
Introduction Due to immature brain development, preterm infants are more likely to develop neurological developmental defects compared with full-term infants. Most preterm infants without neurodevelopmental damage can eventually reach the same scholastic level as their same-age peers; however, some show persistent impairment. Breast feeding (BF), which is an important public health measure, is of great significance for preterm infants. Various active substances in breast milk promote the development of the brain and central nervous system in premature infants. We present a protocol for a prospective longitudinal cohort study to explore the effect of in-hospital BF on brain development in preterm infants and possible influencing factors.Methods and analysis This study will enrol 247 Chinese preterm infants (gestational age: 30–34 weeks) delivered in Women’s Hospital School of Medicine, Zhejiang University, and transferred to the neonatal intensive care unit. Demographic, clinical and in-hospital BF data will be collected through electronic medical records. Moreover, follow-up data will be obtained by telephone, interview or online. Measurements will be obtained using the Breastfeeding Self-Efficacy Scale-Short Form, neuroimaging with functional near-infrared spectroscopy, extrauterine growth restriction and the Ages and Stages Questionnaire. Follow-up will be performed at 3, 6 and 12 months after birth.Ethics and dissemination This study has been approved by the Women’s Hospital School of Medicine Zhejiang University Medical Ethics Committee (2019-058). The study results are expected to be published in peer-reviewed journals and reported at relevant national and international conferences.Trial registration number ChiCTR1900027648; Pre-results.